PENGEMBANGAN MATERI MANAJEMEN STRES SISWA - Dyah Ayu Nurani; Raja Arlizon; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Many of demands and pressure experiences by satudents make it a burden caused by the low bility of stress management. In that regard school have an important role in improving stress management, especially for students in school. But so far the school has not shown efforts to handle it. Therefore, the researchers felt the need to develop a material about Stres Management that is expected to be used by guidance and counseling teacher to be delivered to students. This material is prepared using methods of research and development (R & D). The purpose of this research is 1) Establishment of the material in Stress Management in terms of clarity, systematics, image support, freshness and completeness of the materials and support games / video 2) To determine the quality of material produced. This material is validated by the supervisor 1 & 2 teachers and 40 students Counseling SMPN 13 Pekanbaru. This material is tested to the student with the allocation of a 3-hour lessons (3 x 40 '). This material consists of stress and the mean of stress, stress clasification, symptoms of stress, factors causing stress, the mean of stressor, the source of stress and nature of stressor, and a method to managing stress. The results of the development of this material indicates the quality of the material produced is in the category of " Good", with the acquisition of a score of 4.02 for the entire aspect of the assessment.Key Words: Modul Of Guidance and Counseling, Managing Stress